Anticancer effects of 1’s-1’- acetoxychavicol acetate and its potentiation when conjugated with human alpha fetoprotein against human tumours in Mice / Norhafiza Binti Mohd Arshad - Mohd Arshad, Norhafiza (2015)

(untitled)
Previous in vitro and in vivo studies have reported that 1’S-1’-acetoxychavicol acetate (ACA) and its analogue, 1’S-1’-acetoxyeugenol acetate (AEA) isolated from rhizomes of the Malaysian ethno-medicinal plant Alpinia conchigera Griff (Zingiberaceae) induces apoptosis-mediated cell death in tumour cells via dysregulation of the NF-κB pathway and reduced physiological side effects on non-transformed cells. Nevertheless, there were some clinical development drawbacks such as poor solubility in vivo, depreciation of biological activity and non-specific targeting of tumour cells. In collaborative study with Institute of Engineering Immunology Russia, all the problems above were addressed using their novel drug conjugation technology involving a recombinant human alpha fetoprotein (rhAFP). However, in terms of future cost effectiveness, only ACA which is a major compound was selected for conjugation with rhAFP because AEA being a minor analogue, requires extensive purification steps with very low yield. As examined, thermodynamic studies showed that water soluble rhAFP was successful in retaining non-soluble forms of ACA within its hydrophobic pockets, hence acting as a chaperone which specifically targets tumour cells containing AFP surface receptors. This study also takes advantage of coupling ACA chemopotentiating effect and extrinsic pathway induction together with rhAFP’s specificity and intrinsic pathway induction of apoptosis to increase the efficacy of drugs whilst maintaining a lower dose per se. To study the synergistic effect of both agents on human cancer xenografts, nude athymic (Nu/Nu) mice were used and treated with various combination regimes subcutaneously. It was found that mice exposed to combined treatments displayed higher reductions in tumour volume compared to standalone agents. In addition to this, combined drug treated mice also demonstrated milder signs of systemic toxicity, such as loss in body weight and inflammation of vital organs compared to iii standalone treatments. The immunohistochemistry, ELISA and western blotting results also provided evidence that rhAFP/ACA was not only able to downregulate NF-κB activation, but also reduced the expression of NF-κB regulated genes and inflammatory biomarkers. Therefore, this drug conjugation technology shows great therapeutic potential and a pioneer for the basis of future combination anti-neoplastic drugs development.